Post Total Thyroidectomy Hypocalcaemia and relation with the Age of the Patient - Ahmad, Iftikhar; Malik, M Jalil; Hassan, Mansoor; Naeem, Saquib; Nadeem, Syed farrukh; Hussain, Fayyaz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find the magnitude of clinically overt hypocalcaemia post-total thyroidectomy and its relation with the age of the patient. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital, Bahawalpur Pakistan, from Jan 2017 to Dec 2019. Methodology: Sixty patients who were to undergo total thyroidectomy were included in the study in strict compliance with the inclusion and exclusion criteria. Patients were divided into two groups according to their ages. In Group-A, patients younger than 50 and Group-B, patients older than 50 years were included. All the patients were followed up by clinical examination for the development of clinically overt hypocalcaemia and confirmed by measurement of serum calcium. Results: Mean age of the patients was 42.75±13.05 years, with an age range of 20 to 68 years. Of all the patients, 14(23.3%) were male, and 46(76.7%) were females. Seven patients in Group-A developed post-thyroidectomy hypocalcaemia clinically,whereas, in Group-B, only one developed this condition. Clinical post-thyroidectomy hypocalcaemia developed more often in the younger age group and these results were statistically significant (p= 0.023). Conclusion: Clinically overt hypocalcaemia develops more often in younger patients after total thyroidectomy. Keywords: Biochemical hypocalcaemia, Clinical hypocalcaemia, Post thyroidectomy hypocalcaemia, Total thyroidectomy